Justice matters legacies of the Holocaust and World War II - Weissmark, Mona Sue; Oxford scholarship online (Online service). (New York Oxford University Press, 2004)
Provides insights into ethnic conflicts around the world, such as those in Northern Ireland and the Middle East. This book features stories of how the children of the Holocaust survivors and the children of Nazis struggle to come to terms with the past has universal applications for any society rife with resentment.
Includes bibliographical references and index.
Keywords: Holocaust, Jewish (1939-1945) -- Influence; Holocaust, Jewish (1939-1945) -- Public opinion; Children of Holocaust survivors -- Attitudes; Children of Nazis -- Attitudes; Electronic books; Public opinion -- Germany